2010
DOI: 10.1111/j.1600-6143.2010.03063.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Support: Improves Donor Renal Graft Function After Cardiac Death

Abstract: Donors after cardiac death (DCD) could increase the organ pool. Data supports good long-term renal graft survival. However, DCDs are <10% of deceased donors in the United States, due to delayed graft function, and primary nonfunction. These complications are minimized by extracorporeal support after cardiac death (ECS-DCD). This study assesses immediate and acute renal function from different donor types. DCDs kidneys were recovered by conventional rapid recovery or by ECS, and transplanted into nephrectomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 34 publications
0
26
0
2
Order By: Relevance
“…Cardiac arrest was induced by apnea via ventilator withdrawal and paralytics were given as previously described. [5,7] No heparin was given prior to cardiac arrest and no external heat source was used, to mimic a clinical uDCD setting. Circulatory death was defined as a systolic carotid arterial pressure <20mmHg and a pulse pressure <10mmHg.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac arrest was induced by apnea via ventilator withdrawal and paralytics were given as previously described. [5,7] No heparin was given prior to cardiac arrest and no external heat source was used, to mimic a clinical uDCD setting. Circulatory death was defined as a systolic carotid arterial pressure <20mmHg and a pulse pressure <10mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…[5-8] Our results had shown that room temperature extracorporeal support (ECS) is as effective as 37°C, and that ECS can be used during DCD donation in animals anticoagulated with heparin before or soon after cardiac arrest. This results in conditioning of kidneys, livers and lungs to transplantable status after 30 minutes of WIT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of methods have been offered with this aim: organs cooling by way of the perfusion of cooled preserving liquid through premortum cannulated femoral vessels, applying reperfusion technique for normothermic extracorporeal oxygenation, etc. (9). Legislation is the other opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…These results are exciting, but no other groups have reported similar results. The same group recently published data on a similar model with 30 min of induced warm ischemia followed by ECMO support [66] . Organs were recovered to a transplantable level.…”
Section: In-vivo (In-situ) Perfusionmentioning
confidence: 99%